2020
DOI: 10.3847/1538-4365/ab7894
|View full text |Cite
|
Sign up to set email alerts
|

Physical Parameters of Late-type Contact Binaries in the Northern Catalina Sky Survey

Abstract: We present the physical parameters of 2335 late-type contact binary (CB) systems extracted from the Catalina Sky Survey (CSS). Our sample was selected from the CSS Data Release 1 by strictly limiting the prevailing temperature uncertainties and light-curve fitting residuals, allowing us to almost eliminate any possible contaminants. We developed an automatic Wilson-Devinney-type code to derive the relative properties of CBs based on their light-curve morphology. By adopting the distances derived from CB (orbit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 77 publications
2
80
0
Order By: Relevance
“…They found a mass-ratio of 0.19 for J0305 which is smaller than the estimated value of 0.31 in the present study. However, it should be noted that Sun et al (2020) used only V band data in their analysis and a primary component cooler by 150 K than the present value hence some disagreement between the two estimates could be possible. The total mass (M t ) determined for all the systems is above minimum total mass limit for EWs except for KW Psc.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…They found a mass-ratio of 0.19 for J0305 which is smaller than the estimated value of 0.31 in the present study. However, it should be noted that Sun et al (2020) used only V band data in their analysis and a primary component cooler by 150 K than the present value hence some disagreement between the two estimates could be possible. The total mass (M t ) determined for all the systems is above minimum total mass limit for EWs except for KW Psc.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, in the present analysis, we followed the procedure adopted by Liu et al (2020) for calculating the physical parameters. Recently Sun et al (2020) derived parameters of 2335 late-type contact binaries from the CSS survey including the system J0305. They found a mass-ratio of 0.19 for J0305 which is smaller than the estimated value of 0.31 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Among ∼8 million stars whose time-series data were examined, more than 50,000 objects were selected as candidate variable stars (N. Matsunaga et al, in prep.). In this paper, 7752 candidate variables are considered for our EBS selection, based on Fourier analysis, with periods determined in Section 2.2 (Chen et al 2020).…”
Section: Sample Selectionmentioning
confidence: 99%
“…We selected our EBS sample using the same method as that proposed by Chen et al (2020). Contamination of our sample by non-binary objects is less than 1%, based on careful visual examination.…”
Section: Possible Contamination By Other Variablesmentioning
confidence: 99%
“…Using a much larger sample of CB, Jayasinghe et al (2020) showed that early-type and late-type CB follow a different PL relation. Finally, Sun et al (2020) divided CB into three sub-classes and derived the mid-infrared W 1-band PL relation for each of them.…”
Section: Introductionmentioning
confidence: 99%